Environmental conservation through law enforcement in Sulawesi Barat - Sulaeman Sulaeman; Fatwansyah Rasyid (Indonesia Prime, 2019)
Forests have a very important position and role in the development of Nation and the state. Because forests can provide maximum benefit for the prosperity and welfare of the people. Besides, forests are an invaluable property of the nation and state, so that the country's rights to the forests and the results need to be kept and maintained, and protected through law Enforcement to function properly. Forest is a forest area that has a basic function as a protection of the buffer system of life to regulate water, prevent flooding, control erosion, prevent seawater intrusion, and maintain soil fertility. The effort to protect and secure forest functions is that a effort preserves and protects forest damage and forest outcomes caused by human and livestock deeds, fires, natural powers, pests, and diseases, and maintains and maintains the state rights of forests and forest outcomes. This study resulted in improvements in government policies that gave birth to the strengthening model of protection of damage to forest areas in general and Forest areas in particular